Sequencing-based transcriptome analysis reveals diversification of immune response- and angiogenesis-related expression patterns of early-stage cervical carcinoma as compared with high-grade CIN - Kurmyshkina, Olga V.; Dobrynin, Pavel V.; Kovchur, Pavel I.; Volkova, Tatyana O. (Frontiers in Immunology, 2023)
Molecular diversity of cervical cancer remains an underexplored issue, and immunologic and angiogenic features during the establishment of a particular landscape of its microenvironment are not well-characterized, especially for early clinical stages.We were aimed at identifying transcriptomic landscapes of early-stage cervical carcinoma that differ in their immune-related characteristics, patterns of signaling pathways and composition of the microenvironment in comparison with precursor intraepithelial lesions. We performed RNA sequencing using a panel of fresh tissue samples that included human papillomavirus-positive cervical intraepithelial neoplastic lesions (CIN), invasive squamous carcinoma of the cervix of IA1-IIB stages, and normal epithelium. According to cluster analysis, tissue samples were distributed between three gene expression patterns. Differentially expressed genes were retrieved in each intergroup pairwise comparison followed by Gene Ontology analysis. Gene set enrichment analysis identified substantial differences in immunological and angiogenic properties between tumorous groups. Cell composition analysis confirmed the diverse changes in the abundancies of immune and non-immune populations and, accordingly, different impacts of the immune and stromal compartments on the tumor microenvironment. Positional analysis demonstrated that the identified transcriptomic differences were linked to different chromosomal regions and co-localized with particular gene families implicated in immune regulation, cell differentiation, and tumor invasion. Overall, detection of different transcriptomic patterns of invasive cervical carcinoma at its earliest stages supports the diverse impacts of immune response- and angiogenesis-related mechanisms on the onset of tumor invasion and progression. This may provide new options for broadening the applicability and increasing the efficiency of anti-angiogenic and immune-based therapy of cervical carcinoma.